Multimodal Feedback on speaking: Effectiveness and Students’ Perspective - Syafryadin Syafryadin; Dian Eka Chandra Wardhana (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2021)
Abstract. Multimodal feedback needs to be studied and researched to enhance student’s ability. Thus, this research aims to examine the feedback which using technology and conventional without using technology in speaking, wanted to explore how multimodal feedback could influence the students’ speaking ability, know the student’s perception on multimodal feedback and the reason multimodal feedback could improve students’ speaking ability. The research used a sequential mixed method design with test and interview as instruments. The sample was 54 students for experimental and control group. The result showed that there is not significant different between multimodal feedback with using technology and without using technology. However, in terms of mean score, multimodal feedback with using technology is higher than multimodal feedback without using technology on improving students’ speaking ability. Another result showed that the students had positive response towards the use of multimodal feedback on learning speaking because it can give them much knowledge and upgrade their ability in speaking class. Keywords: Multimodal feedback; using technology; speaking ability